Inferno - Brown, Dan (London Bloomsbury, 2014)
Dan Brown's new novel, Inferno, features renowned Harvard symbologist Robert Langdon and is set in the heart of Europe, where Langdon is drawn into a harrowing world centred around one of history's most enduring and mysterious literary masterpieces
2
Keywords: English stories